Effect of Investment Decisions, Financing Decisions and Dividend Policy on Profitability and Value of The Firm - Sitti Murniati; H. Abdul Rahman Mus; H. Baharuddin Semmaila; Hj. A. Nirwana Nur (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2019)
The purpose of this study is to analyze the effect of investment decisions, financing decisions and dividend policies both directly and indirectly on value of the firm mediated by profitability. The sample technique was purposive sampling by pooling data. Data were analyzed by Structural Equation Modeling. The results showed that investment decisions and financing decisions have a positive and significant effect on profitability and value of the firm so that the main objective of the company is to maximize the welfare of company owners by increasing value of the firm through increased profitability, while dividend policy has a negative and not significant effect on profitability and value of the firm directly and indirectly. Keywords: Investment Decisions, Financing Decisions, Dividend Policies, Profitability and Value of the Firm